Paparan Partikulat Matter (PM10 dan PM2,5) pada Lingkungan Kerja di Pabrik Smelter PT Vale Sorowako, Luwu Timur - Zaenab, Zaenab; Rafidah, Rafidah; Amien, Fiqih Fauziyah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Air is a mixture of gases that surrounds the earth and is an important part of the atmosphere. Air is colorless, odorless, and invisible to the naked eye, but it has mass and volume. Air supports life on earth, providing oxygen for living things, and plays a vital role in various natural processes. Air pollution is currently receiving considerable attention, especially in developing countries and cities with increasing industrialization. Increasing air pollution has a negative impact on human health due to exposure to air pollution. Smelters are where various nickel is processed. Nickel is a strong, corrosion-resistant metal with magnetic properties. Found in various ores, especially laterite and sulfide, nickel is often used in the manufacture of rubber-resistant steel and various industrial products. The nickel mining and processing process can produce pollution through mechanisms involving gas and particle emissions. Air pollution produced by nickel originates from the production process involving the processing of nickel ore which is processed through heating at high temperatures to produce ferronickel or pure nickel. In the area around the PT. Vale Sorowako Luwu Timur industry, there is a high potential for air pollution and health problems originating from nickel industry activities. Health problems can affect the body where particulate matter 10 (PM10) and particulate matter 2.5 (PM2.5) can enter the respiratory tract and reach the lungs and bloodstream which can cause respiratory problems. This study aims to determine the concentration of PM10 and PM2.5 in nickel ore processing production, smelting processes, and workers' rooms at PT Vale Sorowako Luwu Timur. The type of research is descriptive with samples used in the study amounting to 9 measurement points from 3 parts of the smelter factory production. The results of the study showed that the average concentration of PM10 in nickel ore processing production was 1325 µg/m³, the smelting process was 1257 µg/m³, and the workers' room was 1592 µg/m³. and the average concentration of PM2.5 in nickel ore processing production was 555 µg/m³, the smelting process was 764 µg/m³, and the work room was 924 µg/m³. The two highest values were found in the workers' room. Therefore, this study recommends improving ventilation and air filtration systems throughout the production area and conducting regular air quality monitoring.